Evidence of social media accounts in the investigation process - Santoso, Budi (LEGAL BRIEF, 2024)
This study aims to determine the position of electronic evidence in the form of social media accounts in the investigation process and parameters in determining an electronic information/document in the form of social media accounts as evidence in the investigation process. This study uses an empirical legal method with a descriptive approach, utilizing primary and secondary data. The data was collected through observation, document study, and interviews. Furthermore, data analysis is carried out qualitatively. The results of the study show that electronic evidence such as social media accounts has an important role in the investigation of cyber crimes, but it is only considered as valid preliminary evidence if it has gone through official confiscation and digital forensic examination in accordance with the ITE Law. To be accepted in court, electronic evidence must meet formal requirements, namely relevance and validity, as well as material requirements, namely authenticity without modification. Verification through digital forensics is needed to maintain the integrity of evidence, so that electronic evidence is treated as equal to physical evidence in law enforcement